PENGARUH PENGASUHAN IBU DAN NENEK TERHADAP PERKEMBANGAN KEMANDIRIAN DAN KOGNITIF ANAK USIA PRASEKOLAH - Latifah, Eka Wulida; Krisnatuti, Diah; Puspitawati, Herien (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2016)
This study aimed to analyze the influence of the characteristics of children, mothers, and grandmothers; maternal and grandmother parenting style; mother-child and grandmother-grandchild attachment on the development of autonomy and cognitive of preschool children. Participants in this study were 156 respondents (52 preschoolers, 52 working mothers and 52 grandmothers). The data used in this study were primary data (interview and observation method). Processing and analyzing data was done by descriptive (cross tabulation) and inferential (t-test, one way ANOVA and regression) test. The results showed that mothers and grandmothers applied good parenting and attachment. In addition, children were taken care of grandmother have good development of autonomy and cognitive. Research found that the younger mother, the lower level of education of mother and grandmother, the increase of authoritative parenting styles of mother, the decrease of parenting style of authoritarian mother, and the increase of grandmother-grandchild attachment will affect the increase of autonomy of preschool children. Meanwhile, the younger grandmother, the lower education of grandmother, the older children when they were first raised by grandmother, the increase of mother-child and grandmother-grandchild attachment influence significantly the increase of child's cognitive development. The role of the grandmother found to be significant in this study.